A method for manufacturing a battery piece and a battery string
Patent Information
- Application Number
- CN202510527793.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2026-10-30
AI Technical Summary
但是因为传统电池片上的金属栅线中,为了降低金属栅线对电池片的遮光,金属栅线的宽度及串焊条的设计都越来越细
[0028]1、TCO层未设置金属栅线的位置均被所述抗反射层覆盖,相当于传统电池片的一层TCO层被本发明电池片的“一层TCO层+一层抗反射层”所取代,而抗反射层可以降低光的反射率,从而使得与传统电池片相比,所述TCO层可以在传统TCO层的基础上制作得更薄一点,如此,不仅可以降低铟的使用量,进而降低电池片的制作成本;而且还能减短载流子的传递距离,进而提高载流子传导的速度,即提高本发明电池片的效率;
Smart Images

Figure CN123021803A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic products, and in particular to a method for preparing solar cells and solar cell strings. Background Technology
[0002] In traditional battery string assembly fabrication, battery cells are first fabricated by depositing a TCO layer 200 on both the N-side and P-side of a silicon wafer 100. The TCO layer 200 is typically an ITO layer. Then, metal grid lines 300 are fabricated on the TCO layer 200. Multiple battery cells are then string-welded to form the battery string assembly, specifically by welding the metal grid lines 300 to solder them using solder-coated wire rods 400 (e.g.,...). Figure 1 (As shown).
[0003] In solar cells fabricated using this traditional method, the ITO layer has two main properties: it acts as a conductive layer and a light-transmitting layer. The ITO layer laterally transports the electron flow generated by the photoelectric effect, which is then collected, converged, and discharged through metal grid lines. Theoretically, generally speaking, the thinner the ITO film, the less scattering electrons encounter, and the faster the carrier conduction, resulting in better conductivity. Furthermore, since a major component of the ITO layer is indium, which is very expensive, a thinner ITO film requires less indium, thus reducing costs. However, if the ITO layer is too thin, light can easily penetrate and be reflected back, resulting in less light energy being retained by the solar cell, leading to low efficiency. Therefore, to maintain current solar cell efficiency, the ITO layer cannot be made thinner, thus the amount of indium used cannot be reduced, and consequently, costs cannot be lowered.
[0004] Furthermore, because the metal grid lines have no protection, they are prone to oxidation due to contact with moisture and oxygen in the air. This not only affects the conductivity of the metal grid lines, but also causes great problems for subsequent stringing. After stringing, the bond strength between the oxidized copper metal grid lines and the stringing electrodes is much weaker, which ultimately leads to a reduction in the performance of the entire battery string and battery module.
[0005] Furthermore, during string soldering, ideally the soldering electrode should fall precisely on the copper metal grid lines to be soldered (e.g., Figure 1As shown), because the welding rod is generally circular, the advantage of a circular welding rod is that after the light from the solar cell is reflected onto the circular welding rod, it can be reflected again to the surface of the solar cell, resulting in a process of localized incident light (the source of light energy for photoelectric conversion) and localized reflection. Thus, the light-shielding area of the circular welding rod is much smaller than its diameter, which also reduces the light-shielding area of the welding rod and the copper metal grid lines. However, in traditional solar cells, to reduce the light shading of the solar cell by the metal grid lines, the width of the metal grid lines and the design of the welding rod are becoming increasingly thinner. However, current stringing alignment uses an optical alignment mechanism on the stringing machine to align the four edges of the solar cell (after cutting and other processes, a certain proportion of the solar cell is not square or not rectangular). In addition, it is difficult to avoid the cumulative errors generated during production at different stations, ultimately leading to the metal grid lines and the welding rod not being placed in the same position, resulting in stringing misalignment. If the welding rod is still on the metal grid line but only offset to one side (e.g., Figure 2 As shown), the two can still be welded, but the weld bond is extremely weak, and they are prone to detachment, thus affecting the quality of the battery string assembly and subsequent battery modules; if the welding electrode falls directly onto the TCO layer (such as... Figure 3 As shown (indicated), in addition to the weak welding bond mentioned above, the contact resistance at the serial welding point will also increase significantly, thus affecting the conductivity and the efficiency of the solar cell. Furthermore, regardless of the type of offset, it will lead to an increase in the shading area, further reducing the efficiency of the solar cell.
[0006] Furthermore, the copper metal grid lines are not coated with a welding layer; only the welding rods have a welding layer. If the solder on the welding rods is heated unevenly, the melting coverage will be uneven, which will lead to a reduction in the welding bond strength and may also cause a cold solder joint, thus affecting the overall performance of the battery string and battery module. Summary of the Invention
[0007] The purpose of this invention is to overcome the above-mentioned shortcomings and provide a method for preparing battery cells and battery strings. The battery cells and battery strings prepared by this method have low manufacturing costs and guaranteed performance.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a battery cell, characterized in that:
[0010] Includes the following steps:
[0011] S1. Prepare a solar cell with a P-doped layer and an N-doped layer, and deposit a TCO layer on the P-doped layer and the N-doped layer.
[0012] S2. Prepare a patterned mask layer to obtain the trenches;
[0013] S3. Electroplat copper metal grid lines in the trench;
[0014] S4. Deposit a solder layer on each copper metal grid line;
[0015] S5. Remove the mask layer;
[0016] S6. Deposit an anti-reflective layer on the solar cell;
[0017] S7. Remove the anti-reflective layer from the solder layer on the metal grid lines to be soldered.
[0018] The anti-reflective layer is configured as a silicon nitride layer, a silicon oxide layer, or a tin oxide layer.
[0019] The thickness of the anti-reflective layer is 5nm-50nm.
[0020] Picosecond lasers were used to remove the anti-reflective layer, and the parameters for this removal were set as follows: power density of 1.0-3.0 J / cm². 2 The frequency is 50-150kHz, the spot size is set to 10um-50um, and the scanning speed is 0.5-2m / s.
[0021] The TCO deposition layer is obtained by depositing a single TCO material among AZO, IWO, or ITO; or, it is obtained by depositing a composite TCO material of two or three of AZO, IWO, and ITO.
[0022] The thickness of the weld layer is 0.1um-5um.
[0023] After step S1 and before step S3, a seed layer is deposited on the TCO layer; after removing the mask layer and before preparing the anti-reflection layer, the seed layer not between the copper metal gate line and the TCO layer is removed.
[0024] A method for preparing a battery string assembly involves feeding at least two battery cells prepared by the above method into a string welding machine and aligning them, then stacking welding rods on the exposed copper metal grid lines to be wired for welding, and then performing the string welding process.
[0025] Align the solar cells according to the position of the metal grid lines to be wired.
[0026] The outer surface of the welding electrode is covered with solder, and the material of the solder is the same as that of the welding layer on the copper metal grid.
[0027] Because the present invention employs the above-mentioned technical solution, the resulting battery cells and battery string groups have the following beneficial technical effects:
[0028] 1. The TCO layer without metal grid lines is covered by the anti-reflection layer, which is equivalent to replacing the TCO layer of a traditional solar cell with "one TCO layer + one anti-reflection layer" in the solar cell of this invention. The anti-reflection layer can reduce the reflectivity of light, so the TCO layer can be made thinner than the traditional TCO layer. This not only reduces the amount of indium used, thereby reducing the manufacturing cost of the solar cell, but also shortens the carrier transmission distance, thereby increasing the carrier conduction speed, that is, improving the efficiency of the solar cell of this invention.
[0029] 2. The anti-reflective layer can isolate the TCO layer from moisture and oxygen in the air, thereby ensuring the stability of the ITO layer's performance, which in turn ensures the stability of the cell's performance.
[0030] 3. The anti-reflective layer on the weld layer of the metal grid line that does not need to be welded to the welding rod is not removed. Therefore, this part of the metal grid line is completely covered under the anti-reflective layer. That is, the anti-reflective layer isolates this part of the metal grid line from the moisture and oxygen in the air, thereby preventing the metal grid line from oxidizing. Although the anti-reflective layer on the copper metal grid line to be welded is removed, because there is a weld layer on it, and its two sides and the two sides of the weld layer are still covered with anti-reflective layers, the weld layer and the anti-reflective layer together isolate the metal grid line to be welded to the welding rod from the moisture and oxygen in the air, preventing it from being oxidized and affecting the firmness of the subsequent welding.
[0031] 4. Because the anti-reflective layer on the metal grid lines to be welded to the wire rod is removed, the welding layer on these copper metal grid lines is exposed, eliminating the need to remove the anti-reflective layer on the welding layer of the metal grid lines to be welded to the wire rod. Thus, the entire cell only exposes the grid lines to be welded, and these grid lines form a higher resolution optical contrast with the overall cell background color. Therefore, during subsequent wire welding alignment, the actual position of the metal grid lines to be welded can be used instead of the original edge of the cell as the optical alignment reference, thereby achieving more accurate wire welding alignment and avoiding misalignment of the wire rod relative to the copper metal grid lines to be welded, thus avoiding problems caused by wire rod misalignment.
[0032] 5. After the aforementioned optical alignment system performs more precise stringing alignment based on the location of the copper metal grid lines to be wired, even if there are still slight offsets, the slight offsets can be corrected by the micro-traction phenomenon between the same material when the welding layer on the grid lines and the solder on the wired welding rod are made of the same tin material, because the two are fused by heating. Furthermore, since both contact layers are in a molten state, faster and better bonding can be achieved, thereby further reducing the occurrence of stringing offsets, ensuring more precise stringing alignment, and thus ensuring the bonding strength after stringing, reducing the light shading rate of the solar cells, ensuring the light absorption rate of the solar cells, that is, ensuring the efficiency of the solar cells, and thus ensuring the overall performance of the battery string and battery module.
[0033] 6. Because the copper metal grid lines to be welded to the welding rods have a welding layer, even if the solder on the welding rods is heated unevenly during the welding process, resulting in uneven molten coverage, the solder in the welding layer on the copper metal grid lines will also melt. This improves the uniformity of the overall solder molten coverage, allowing for more uniform and faster welding, reducing the possibility of incomplete welds, and further improving the welding bond between the copper metal grid lines and the welding rods, thus ensuring the overall performance of the battery string and battery module. Attached Figure Description
[0034] Figure 1 A schematic diagram illustrating the precise alignment of the welding electrodes for the battery cells;
[0035] Figure 2 This is a schematic diagram illustrating the positional deviation between the welding rods and the metal grid lines to be welded in a traditional solar cell.
[0036] Figure 3 This is a schematic diagram showing the deviation of the wire bonding electrode of a traditional solar cell falling onto the TCO layer;
[0037] Figure 4 This is a schematic diagram of the battery cell of the present invention;
[0038] Figure 5 This is a schematic diagram of the battery cell of the present invention after the seed layer has been deposited;
[0039] Figure 6 This is a schematic diagram of the battery cell of the present invention after the patterned mask layer has been prepared;
[0040] Figure 7 This is a schematic diagram of the battery cell of the present invention after the copper metal grid lines and welding layers are fabricated;
[0041] Figure 8 This is a schematic diagram of the battery cell of the present invention after the mask layer and seed layer have been removed;
[0042] Figure 9 This is a schematic diagram of the battery cell after the anti-reflection layer has been deposited according to the present invention;
[0043] Figure 10 This is a schematic diagram of the battery string assembly of the present invention. Figure 1 ;
[0044] Figure 11 This is a schematic diagram of the battery string assembly of the present invention. Figure 2 ;
[0045] Figure 12 This is a schematic diagram of a traditional solar cell;
[0046] Figure 13 This is a schematic diagram of a battery cell prepared using the method of the present invention;
[0047] Figure 14 This is a schematic diagram of the battery string assembly of the present invention;
[0048] Figure 15 This is a schematic diagram showing a misaligned solder joint in a traditional battery string assembly. Detailed Implementation
[0049] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0050] This invention discloses a method for preparing a battery cell, which includes the following steps:
[0051] S1. Prepare a solar cell with a pre-fabricated P-doped layer 3 and N-doped layer 2, and deposit an ITO layer (e.g., ...) on the P-doped layer 3 and N-doped layer 2. Figure 5 (as shown);
[0052] S2. Prepare a patterned mask layer 9 to obtain trenches 10 (e.g., Figure 6 (as shown);
[0053] S3, Electroplating copper metal grid lines 5 (such as...) within the trench 10 Figure 7 (as shown);
[0054] S4. Deposit a solder layer 6 (e.g., on each copper metal grid line 5) on each copper metal grid line 5. Figure 7 (as shown);
[0055] S5, Remove mask layer 9 (e.g.) Figure 8 (as shown);
[0056] S6. Deposit an anti-reflective layer 7 on the solar cell (e.g.) Figure 9 (as shown);
[0057] S7. Remove the anti-reflective layer 7 from the welding layer 6 on the metal grid lines to be wired.
[0058] The above steps can be used to fabricate a solar cell 500. The solar cell 500 includes a silicon wafer 1, an N-doped layer 2, a TCO layer 4, and copper metal grid lines 5 sequentially disposed on the front side of the silicon wafer 1, and a P-doped layer 3, a TCO layer 4, and copper metal grid lines 5 sequentially disposed on the back side of the silicon wafer 1. A solder layer 6 is provided on the copper metal grid lines 5. Some of the copper metal grid lines 5 are designated as metal grid lines to be soldered, i.e., they are to be subsequently soldered to the soldering rods 11. Except for the top of the solder layer 6 on these copper metal grid lines 5, the other areas of the front and back sides of the solar cell 500 are covered with an anti-reflective layer 7. That is, only the top of the solder layer 6 on the copper metal grid lines 5 to be soldered is not covered by the anti-reflective layer 7 (e.g., ...). Figure 4 (As shown).
[0059] In step S1, the solar cell with the prepared P-doped layer 3 and N-doped layer 2 can be fed into a PVD device for TCO layer deposition to obtain the TCO layer. During the deposition operation, the PVD deposition power is set to 1 kW-10 kW, and the deposition time is 30 seconds-600 seconds. The thickness of the obtained TCO layer 4 is 5 nm-150 nm. Preferably, the thickness of the TCO layer 4 can be 10, 15, 20, 30, 35, 40, 50, 55, 60, 65, 70, 80, 90, 100, 110, 120, 130, 140, or 145 nm.
[0060] The TCO deposition layer can be obtained by depositing a single TCO material among AZO, IWO, or ITO, or by depositing a composite TCO material of two or three of AZO, IWO, and ITO. That is, the TCO deposition layer of the fabricated solar cell can be a single AZO layer, IWO layer, or ITO layer, or a composite layer of two or three of AZO, IWO, and ITO.
[0061] Preferably, during deposition, using AZO material with a ratio of (ZnO:Al2O3 = 90:10)-(ZnO:Al2O3 = 99:1) can yield a single AZO deposition layer; using IWO material with a ratio of (In2O3:W = 90:10)-(In2O3:W = 99:1) can yield a single IWO deposition layer; and using ITO material with a ratio of (In2O3:SnO2 = 90:10)-(In2O3:SnO2 = 99:1) can yield a single ITO deposition layer.
[0062] In one embodiment, ITO material with the above-mentioned ratio is used for deposition, and the deposition power is set to 1KW and the deposition time is 1 minute, so that an ITO deposition layer with a thickness of 35nm can be obtained.
[0063] In step S2, a mask layer 9 is coated onto the battery cell, and after curing the mask layer 9, exposure and development operations are performed to obtain a patterned mask layer 9 (e.g., ...). Figure 6 (As shown). In this embodiment, the thickness of the mask layer 9 is 13um-15um.
[0064] Specifically, a mask is applied to the battery cells that have completed the previous steps using a printing process, and then dried and cured under atmospheric conditions. During curing, the temperature is set to 90℃-100℃, and the curing time is 400-750 seconds.
[0065] The exposure can be performed using a direct-write exposure machine (commonly known as LDI), and during exposure, the wavelength range is 355nm-365nm, and the exposure energy range is 145mj / cm2-150mj / cm2, thereby completing the pattern transfer process.
[0066] The developing process uses sodium carbonate with a concentration of 1.2%-1.5%, a developing temperature of 30℃-35℃, a spray pressure range of 3.0Kg / cm2-3.5Kg / cm2, and a developing time of 150-280 seconds.
[0067] After the patterned mask layer 9 is prepared, a groove 10 is naturally formed between the mask layer 9 and the battery cell, in preparation for the subsequent electroplating of copper metal grid lines 5.
[0068] The electroplated copper metal grid line 5 in step S3 can be produced using any known and feasible technology, so it will not be described in detail here.
[0069] The thickness of the copper metal grid line 5 is 5µm-25µm; preferably, the thickness of the copper metal grid line 5 is 6µm-8µm. The thickness of the copper metal grid line 5 can also be 10, 12, 15, 18, 20, 22, or 24µm. The width of the metal grid line to be wired is in the range of 10µm-300µm, so as to better adapt to the wired welding rod 11. In this embodiment, the metal grid line includes a main grid 51 and a fine grid 52 (combined with...). Figure 4 and Figure 11 As shown in the figure, the width of the main grid 51 is 50-100 μm, and the width of the fine grid 52 is 15 μm; the main grid 51 is configured to be subsequently welded to the welding rod 11. In other embodiments, other grid lines can also be configured as metal grid lines to be welded according to actual needs.
[0070] In step S4, depositing the solder layer 6 can be achieved using an electroplating process, whereby the solder layer 6 is electroplated onto each copper metal gate line 5 (e.g., ...). Figure 7 (as shown); alternatively, the battery cell with the prepared copper metal grid 5 can be fed into a PVD device for chemical deposition of the welding layer 6.
[0071] During PVD deposition, the deposition power is set to 1.5-2.5 kW, the deposition temperature to 150-260 °C, and the deposition time to 180-360 seconds. Preferably, the power is set to 2 kW, the deposition temperature to 200 °C, and the deposition time to 300 seconds.
[0072] In this embodiment, the welding layer 6 is set as a solder layer, that is, tin is used for electroplating or chemical deposition, balancing welding performance and cost. The thickness of the welding layer 6 is 0.1um-5um. Preferably, the thickness of the welding layer 6 is 0.5um-1um. The thickness of the welding layer 6 can also be 0.2, 0.8, 1.5, 2, 2.5, 3, 3.5, 4, or 4.5um. In other embodiments, the welding layer 6 can also be made of other welding materials. The thickness of the welding layer 6 is set in this way because the subsequent soldering rods are also covered with a layer of solder. If the welding layer 6 is too thin, it will not play its corresponding role; if it is too thick, it will be wasteful because some metal grid lines do not need to be soldered. Therefore, this thickness setting is more appropriate.
[0073] In step S5, the mask layer 9 can be removed using sodium carbonate with a concentration of 2.8%-3%, at a temperature of 60℃-65℃, a spray pressure of 3.0Kg / cm2-3.5Kg / cm2, and a time of 220-360 seconds.
[0074] In step S6, the solar cell, having completed the preceding steps, is loaded into a vacuum deposition apparatus (including but not limited to PECVD, PVD, and CVD) to deposit an anti-reflection layer 7. The anti-reflection layer 7 may be, but is not limited to, a silicon nitride (SiNx) layer, a tin oxide (SnOx) layer, or a silicon oxide (SiOx) layer. The silicon nitride, silicon oxide, or tin oxide layer can reduce light reflectivity.
[0075] The thickness of the anti-reflective layer 7 is 5nm-150nm. Further, the thickness of the anti-reflective layer 7 is set to 10, 20, 30, 40, 60, 70, 80, 90, 100, 120, 130 or 140nm.
[0076] When preparing the silicon nitride antireflective layer 7, it can be obtained through PEVCD deposition. Specifically, the solar cell, after completing the preceding steps, is fed into a plasma-enhanced chemical vapor deposition (PECVD) apparatus to deposit the silicon nitride layer. The deposition conditions are set as follows: temperature 180℃-200℃, pressure 1.8 Torr-2 Torr, gas precursors of silane (SiH4), ammonia (NH3), and nitrogen (N2), with a flow rate ratio of SiH4:NH3:N2 = 1:5:5; radio frequency (RF) power 38W-58W, RF frequency 13.56MHz, and deposition time 200-400 seconds. This yields a silicon nitride layer with a thickness of 5-50 nm.
[0077] The silicon nitride antireflective layer 7 can also be obtained by CVD chemical vapor deposition. Specifically, the solar cell that has completed the preceding steps is loaded into the CVD equipment, and the deposition conditions are set as follows:
[0078] Using SiH4 as the silicon source and ammonia (NH3) as the nitrogen source, with a SiH4 to NH3 flow rate ratio of 1:3 to 1:5 and a total flow rate of 5-70 sccm, and oxygen as the oxygen source, with an oxygen flow rate of 50-500 sccm, the deposition temperature is set to 200℃-800℃, and the deposition time is 30-600 seconds. This yields silicon nitride layers with a thickness of 5nm-10nm.
[0079] When preparing the silicon oxide antireflective layer 7, it can be obtained by CVD chemical vapor deposition. The solar cell that has completed the previous steps is loaded into the CVD equipment for deposition, and the deposition conditions are set as follows:
[0080] Using SiH4 as the silicon source, the SiH4 flow rate is 5-70 sccm; using oxygen as the oxygen source, the oxygen flow rate is 50-500 sccm; the deposition temperature is 200℃-800℃, the deposition time is 30sec-600sec, and a silicon oxide antireflective layer 7 is generated, with a thickness of 5nm-10nm.
[0081] To prepare the tin oxide antireflective layer 7, it can be fabricated using vacuum deposition (PVD) with a tin oxide target. During deposition, the power is set to 1-2 kW, the deposition temperature to 180-200°C, and the deposition time to 30-300 seconds. This yields the tin oxide antireflective layer 7 with a thickness of 5-65 nm.
[0082] In step S7, since a portion of the copper metal grid line 5 is configured to be welded to the welding rod 11 in subsequent operations, the welding layer 6 of this portion of the copper metal grid line 5 needs to be exposed and not covered by the anti-reflective layer 7. Therefore, the anti-reflective layer 7 at the corresponding position needs to be removed.
[0083] The anti-reflective layer 7 can be removed using laser technology; preferably, a picosecond laser with a wavelength of 355nm ultraviolet light is used. During operation, the solar cell is fed into a picosecond laser device with a wavelength of 355nm ultraviolet light, and the parameters for removing the anti-reflective layer using the picosecond laser are set as follows: power density of 1.0-3.0 J / cm². 2 The frequency is 50-150kHz, the spot size is set to 10um-50um, and the scanning speed is 0.5-2m / s. This setting allows for more precise control over the thickness removed, meaning that only the anti-reflective layer at the corresponding location can be removed without damaging the solder layer.
[0084] In one embodiment, the optical power density is set to 1.3 J / cm². 2The frequency was set to 100kHz, the spot width was 35µm or 50µm, and the scanning speed was 2m / s.
[0085] In another embodiment, the optical power density of the picosecond laser device is set to 1.2 J / cm². 2 The frequency was set to 80kHz, the spot width was set to 30µm, and the scanning speed was 1.5m / s.
[0086] In another embodiment, the optical power density of the picosecond laser device is set to 1.3 J / cm². 2 The frequency was set to 150kHz, the spot width was 30µm, and the scanning speed was set to 2m / s.
[0087] The picosecond laser device described above scans the positions of the copper metal grid lines 5 to be strung on the solar cell, removing the anti-reflective layer 7 from these copper metal grid lines 5 and exposing the solder layer. Thus, among all the copper metal wires, the top of the copper metal wires to be strung is free of the anti-reflective layer 7, while the tops of the other copper metal grid lines 5 are still covered by the anti-reflective layer 7. That is to say, only the grid lines to be strung are exposed on the entire solar cell, and these grid lines create a higher resolution optical contrast with the overall background color of the solar cell. Therefore, during subsequent optical alignment during stringing, the actual grid line positions to be strung can be used instead of the original edge of the solar cell as the optical alignment reference, thereby achieving more precise stringing alignment.
[0088] Furthermore, because the main grid is set as copper metal grid lines to be soldered, after removing the anti-reflective layer 7 on top, the fine grids on the solar cell are almost invisible to the naked eye (e.g., Figure 13 As shown, the vertical lines represent the main grid, and the horizontal lines represent the fine grid. Only the main grid after the anti-reflective layer has been removed using a laser is clearly visible. This differs from traditional solar cells (such as...). Figure 12 The difference (as shown) is very obvious, from Figure 12 As can be seen, the fine grids on traditional solar cells are also very obvious. Compared to the past, the solar cells produced by the method of this invention are more aesthetically pleasing and have less color difference.
[0089] Preferably, the method for preparing the battery cell of the present invention further includes:
[0090] After step S1 and before step S3, a seed layer 8 is deposited on the TCO layer. Specifically, the solar cell with the fabricated TCO layer is loaded into a PVD apparatus, and a seed layer 8 deposition process is performed on the TCO layer. This seed layer 8, like the TCO layer, is a continuous, single layer (e.g., ...). Figure 5 (As shown). Seed layer 8 includes, but is not limited to, metals such as gold, silver, copper, titanium, nickel, tungsten, and bismuth deposited or alloys thereof deposited; and the thickness of seed layer 8 is in the range of 5nm-150nm.
[0091] When depositing the seed layer 8, the deposition conditions are set as follows: power of 1KW-10KW and deposition time of 30 seconds-600 seconds. In one embodiment, taking the seed layer 8 as a copper metal layer as an example, the power is set to 3KW and the deposition time is set to 3 minutes, thus obtaining a copper seed layer 8 with a thickness of 100nm covering the ITO layer.
[0092] If the seed layer 8 is not provided, the above process involves fabricating the patterned mask layer 9 on the TCO layer. If the seed layer 8 is provided, the process involves fabricating the patterned mask layer 9 on the seed layer 8.
[0093] Furthermore, if the seed layer 8 is to be prepared, the excess seed layer 8 needs to be removed after removing the mask layer 9 and before preparing the anti-reflection layer 7. Specifically, the seed layer 8 not located between the copper metal gate line 5 and the TCO layer 4 is removed, and only the seed layer 8 between the copper metal gate line 5 and the TCO layer 4 is retained (e.g., Figure 4 , 8 (As shown).
[0094] Excess seed layer can be removed by sulfuric acid at a concentration of 1%-2%, a temperature of 30℃-35℃, a spray pressure of 1-1.5Kg / cm2, and a time of 50-300 seconds.
[0095] Thus, the solar cell prepared by the method of the present invention also includes a seed layer disposed between the copper metal grid lines 5 and the TCO layer 4. The seed layer 8 enhances the bonding force between the copper metal grid lines 5 and the TCO layer 4, making it less likely for the copper metal grid lines 5 to detach from the solar cell, thereby ensuring the photoelectric conversion efficiency of the solar cell.
[0096] Each of the above steps is for processing one side of the solar cell. To process both sides, one side is processed first, and then the other side is processed.
[0097] like Figure 10 , 11 As shown, the present invention also discloses a method for preparing a battery string assembly. To prepare the battery string assembly, at least two battery cells are fed into a stringer and aligned. Then, a stringer electrode 11 is stacked on the exposed welding layer 6 of the copper metal grid lines 5 to be stringed, so that the stringer electrode 11 is in contact with the welding layer 6 of the copper metal grid lines 5. A stringing process is then performed to obtain the battery string assembly. In this embodiment, because the main grid is set as the copper metal grid lines to be stringed, the stringer electrode 11 is stacked and connected to the main grid.
[0098] In this embodiment, preferably, because the metal grid lines to be strung on the battery cell of the present invention form a higher resolution optical contrast with the overall background color of the battery cell, the optical alignment system of the stringer can optically align the battery cell according to the position of the copper metal grid lines 5 to be strung on. That is to say, the basis of optical alignment is changed from the four edges of the traditional battery cell to the welding layer 6 exposed on top of the copper metal grid lines 5 to be strung on. In this way, the position where the stringer bars 11 are to be stacked can be more accurately aligned, thereby avoiding a large offset between the stringer bars 11 and the copper metal grid lines 5 to be strung on, and thus avoiding problems caused by the offset of the stringer bars 11. The above-mentioned optical alignment principle is a well-known technology, so it will not be described in detail here.
[0099] The battery string assembly prepared by the above method includes a welding rod 11 and at least two of the aforementioned battery cells. The welding rod 11 is stacked and connected to the copper metal grid lines 5 exposed in the welding layer 6. In this embodiment, since the main grid is set as the copper metal grid lines to be welded, the welding rod 11 is stacked and connected to the main grid.
[0100] The heat source of the stringer is infrared radiation. During stringing, the infrared wavelength is set to 0.76μm-1.6μm, the temperature is set to 80℃-200℃, and the infrared irradiation time is 2-5 seconds. In one embodiment, after the battery cells are loaded onto the stringer table and optically aligned, the temperature is set to 130℃ and the downward pressure is set to 1.5Kg / cm. 2 The battery cells and the welding rod 11 were welded together under the condition of an irradiation time of 3 seconds.
[0101] The welding rod 11 is a circular welding rod with a diameter of 120um-250um, and the outer surface of the welding rod 11 is covered with a layer of solder with a thickness of 1um-10um. Preferably, the material of the solder is the same as the material of the welding layer 6 on the copper metal grid line 5. With this configuration, after the aforementioned optical alignment system performs more precise welding alignment based on the position of the copper metal grid line 5 to be welded, even if there is still a slight offset, because the welding layer on the grid line and the solder on the welding rod are made of the same tin material, the micro-traction phenomenon between the same substances can also correct the slight offset when heated to fuse them. Furthermore, since both contact layers are in a molten state, faster and better bonding can be achieved, thereby further reducing the occurrence of welding offset and ensuring more precise welding alignment, such as... Figure 14 The image shows the battery string assembly after precise alignment and welding according to the present invention; as shown Figure 15 The diagram shown illustrates the issue of misaligned solder joints in traditional battery string arrays. Figure 15It is evident that there is a significant positional misalignment between the welding rod and the metal grid lines to be welded. Precise alignment of the two avoids the problem of increased shading rate of the solar cells caused by the misalignment of the welding rod 11, ensuring the light absorption rate of the solar cells, i.e., ensuring the efficiency of the solar cells, and thus ensuring the overall performance of the battery string assembly; it also ensures the bonding strength after welding. Furthermore, because the copper metal grid lines 5 to be welded have a welding layer 6, even if the solder on the welding rod 11 is heated unevenly during welding, resulting in uneven melting and coverage, the solder on the welding layer 6 of the copper metal grid lines 5 will also melt. Thus, the solder from both parts can completely cover the welding surface of the welding rod and the copper metal grid lines, reducing the possibility of incomplete welding, thereby improving the welding bonding strength between the copper metal grid lines 5 and the welding rod 11, further ensuring the overall performance of the battery string assembly.
[0102] As described above, the solar cell produced by the method of the present invention has its TCO layer 4, where no metal grid lines are provided, covered by the anti-reflection layer 7. This is equivalent to replacing the traditional TCO layer 4 with "one TCO layer 4 + one anti-reflection layer 7" in the solar cell of the present invention. The anti-reflection layer 7 can reduce the reflectivity of light, so compared with the traditional solar cell, the TCO layer 4 of the solar cell of the present invention can be made thinner, and the thickness can be selected within the range of 5nm-150nm. In this way, not only can the amount of indium used be reduced, thereby reducing the manufacturing cost of the solar cell, but the carrier transmission distance can also be shortened, thereby increasing the carrier conduction speed, that is, improving the efficiency of the solar cell of the present invention. The thickness of the TCO layer 4 and the anti-reflection layer 7 are set as described above, so that the overall refractive index of the solar cell of the present invention can be maintained between 2.0% and 2.1%. The low refractive index can improve the light energy rejection rate, thereby improving the efficiency of the solar cell.
[0103] Furthermore, the anti-reflective layer 7 can isolate the TCO layer 4 underneath it from moisture and oxygen in the air, thereby ensuring the stability of the ITO layer performance, that is, ensuring the stability of the battery cell performance. In addition, the anti-reflective layer 7 can isolate the copper metal grid lines 5 underneath it from moisture and oxygen in the air, thereby preventing oxidation of the metal grid lines. Although the anti-reflective layer 7 on the copper metal grid lines to be wired is removed, because there is a welding layer 6 on it, and its two sides and the two sides of the welding layer 6 are still covered by the anti-reflective layer 7, the welding layer 6 and the anti-reflective layer 7 together isolate the metal grid lines to be wired with the wire bonding bar 11 from moisture and oxygen in the air, preventing them from being oxidized and affecting the firmness of the subsequent wire bonding, thereby ensuring the performance of the battery string.
[0104] The present invention also discloses a battery module, which includes the above-mentioned battery cells or battery strings.
[0105] To prepare the battery module, the battery string group, encapsulation mold, backplate, and glass are arranged according to the lamination process requirements and then the components are laminated. The lamination time is set to 5-30 minutes, the lamination temperature is 180℃-220℃, and the lamination pressure is 0.5MPa-1.5MPa to obtain the battery module.
[0106] In one embodiment, the lamination time is 20 minutes, the lamination temperature is 200°C, and the lamination pressure is 1.0 MPa.
[0107] In other embodiments, the lamination time can be set to 8, 10, 15, 18, 22, 25 or 28 minutes, the lamination temperature can be set to 190, 195, 205, 210 or 215°C, and the lamination pressure can be set to 0.8, 0.9, 1.2, 1.3 or 1.4 MPa.
[0108] The lamination process can be a conventional technical solution, so it will not be described in detail here.
[0109] Because the battery cells and battery strings produced by the method of this invention have the aforementioned beneficial technical effects, the battery modules produced also have corresponding beneficial technical effects.
[0110] The embodiments of the present invention have been described in detail above, but the content described is only a preferred embodiment of the present invention and should not be considered as limiting the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the patent coverage of the present invention.
Claims
1. A method for preparing a battery cell, characterized in that: Includes the following steps: S1. Prepare a solar cell with a P-doped layer and an N-doped layer, and deposit a TCO layer on the P-doped layer and the N-doped layer. S2. Prepare a patterned mask layer to obtain the trenches; S3. Electroplat copper metal grid lines in the trench; S4. Deposit a solder layer on each copper metal grid line; S5. Remove the mask layer; S6. Deposit an anti-reflective layer on the solar cell; S7. Remove the anti-reflective layer from the solder layer on the metal grid lines to be soldered.
2. The method for preparing a battery cell according to claim 1, characterized in that: The anti-reflective layer is configured as a silicon nitride layer, a silicon oxide layer, or a tin oxide layer.
3. The method for preparing the battery cell according to claim 1 or 2, characterized in that: The thickness of the anti-reflective layer is 5nm-50nm.
4. The method for preparing the battery cell according to claim 3, characterized in that: Picosecond lasers were used to remove the anti-reflective layer, and the parameters for this removal were set as follows: power density of 1.0-3.0 J / cm². 2 The frequency is 50-150kHz, the spot size is set to 10um-50um, and the scanning speed is 0.5-2m / s.
5. The method for preparing a battery cell according to claim 1, 2, or 4, characterized in that: The TCO deposition layer is obtained by depositing a single TCO material among AZO, IWO, or ITO; or, it is obtained by depositing a composite TCO material of two or three of AZO, IWO, and ITO.
6. The method for preparing a battery cell according to any one of claims 1 to 5, characterized in that: The thickness of the weld layer is 0.1um-5um.
7. The method for preparing a battery cell according to any one of claims 1 to 6, characterized in that: After step S1 and before step S3, a seed layer is deposited on the TCO layer; after removing the mask layer and before preparing the anti-reflection layer, the seed layer not between the copper metal gate line and the TCO layer is removed.
8. A method for preparing a battery string assembly, characterized in that: At least two solar cells, prepared by any one of claims 1 to 7, are fed into a stringer and aligned. Then, stringing electrodes are stacked on the exposed copper metal grid lines to be strung, and the stringing process is performed.
9. The method for preparing a battery string according to claim 8, characterized in that: Align the solar cells according to the position of the metal grid lines to be wired.
10. The method for preparing a battery string according to claim 8 or 9, characterized in that: The outer surface of the welding electrode is covered with solder, and the material of the solder is the same as that of the welding layer on the copper metal grid.
